Phytochemical and chemotaxonomic study on Dianella ensifolia (L.) DC. (June 2017) - Tang, Ben-qin; Chen, Zhen-yang; Sun, Jian-bo; Lee, Simon Ming-yuen; Lu, Jian-lin
Abstract: Phytochemical investigation of the roots of Dianella ensifolia led to the isolation of eleven known compounds, including two aromatics (1, 2 ), two chromones (3, 4 ), and seven flavonoids (5 –11 ). The structures of these compounds were elucidated on the basis of spectral analysis and comparison with data reported in literature. In the present research, all of the isolated compounds1 –11 were reported for the first time in the species D. ensifolia . Compounds1 –4 and7 –11 were firstly isolated from the genus Dianella . Compounds1, 2, 8, and9 have not been reported from any species in Liliaceae family. The chemotaxonomic significance of the isolated compounds was summarized. Highlights: Eleven compounds were isolated from Dianella ensifolia. Compounds1–11 were obtained from D. ensifolia for the first time. Compounds1 –4 and7 –11 were isolated from the genus Dianella for the first time. Compounds1, 2, 8 and9 were firstly reported from family Liliaceae. The chemotaxonomic significance of the isolates was discussed.